The Effect of Moringa Oleifera Extract on Melatonin Levels and Skin Cell Images in Rattus Novergicus Exposed to Ultraviolet Rays - Irma Rosalina; Harliansyah; Ira Kusumawaty (Postgraduate, University of Mataram, 2025)
Exposure to ultraviolet (UV) light has negative effects on skin health, including decreased melatonin levels and increased skin cell damage. This study investigated the effects of Moringa oleifera (MO) leaf extract on melatonin levels and skin damage induced by UVB light in male Sprague Dawley rats. Utilizing a post-randomized controlled group design, 28 rats were allocated into four groups: a control group without treatment and a treatment group subjected to UVB exposure alongside MO extract at doses of 300 mg/kg and 600 mg/kg. Melatonin levels were quantitatively assessed via spectrophotometry, while histopathological analysis was employed to evaluate skin damage. Results indicated that rats receiving the 600 mg/kg MO extract exhibited the highest melatonin levels, contrasting sharply with the group exposed solely to UVB radiation, which showed significantly reduced melatonin. Histological examination revealed a marked decrease in sunburn cell lesions in the MO extract-treated group compared to the control group lacking treatment. In conclusion, Moringa oleifera leaf extract appears to enhance melatonin production and mitigate UV-induced skin damage, suggesting its potential as a protective agent in dermatological practices. These findings warrant further exploration into the application of MO extract in developing preventive therapies against UV-related skin damage.